Perineural Dexmedetomidine as an Adjuvant Reduces the Median Effective Concentration of Lidocaine for Obturator Nerve Blocking: A Double-Blinded Randomized Controlled Trial. - Yuechun Lu; Jian Sun; Xinqi Zhuang; Guoyi Lv; Yize Li; Haiyun Wang; Guolin Wang (PLoS ONE, 2016)
Research suggests that the addition of dexmedetomidine to local anesthetics can prolong peripheral nerve blocks; however, it is not known whether dexmedetomidine can reduce the quantity of local anesthetic needed. We hypothesized that adding dexmedetomidine as an adjuvant to an obturator nerve block could reduce the median effective concentration of lidocaine. In this double-blinded randomized trial, 60 patients scheduled for elective transurethral resection of bladder tumors on the lateral wall were randomly divided into two groups: the control group (C group, n = 30) and the dexmedetomidine group (D group, n = 30). Two main branches of the obturator nerve (i.e., anterior and posterior) were identified using neural stimulation at the inguinal level, with only lidocaine used for the C group and 1 μg/kg dexmedetomidine combined with lidocaine used for the D group. The median effective concentration was determined by an up-and-down sequential trial. The ratio of two consecutive concentrations was 1.2. The median effective concentration (95% confidence interval) of lidocaine was 0.57% (0.54%-0.62%) in the C group and 0.29% (0.28%-0.38%) in the D group. The median effective concentration of lidocaine was significantly lower in the D group than in the C group (p < 0.05). These results indicate that dexmedetomidine (1 μg/kg) in combination with lidocaine for obturator nerve block decreases the median effective concentration of lidocaine.ClinicalTrials.gov NCT02066727.